Noise Correlation Spectroscopy for spectroscopic measurements of low energy modes - Sparapassi, Giorgia; Tollerud, Jonathan Owen; Glerean, Filippo; Fausti, Daniele (2018 Conference on Lasers and Electro-Optics, CLEO 2018 - Proceedings, 2018)
Noise Correlation Spectroscopy (NCS) is a technique exploiting statistical correlations imprinted onto spectral components of shaped ultrashort light pulses by a light-matter inelastic scattering process, in order to measure low energy eigenmodes of a material.
CRIS-Team Scopus Importer:2022-07-20